THE USAGE OF VANDERVEKEN THEORY TO ANALYSE ILLOCUTIONARY ACTS ON THE “OPINION” COLUMN OF THE JAKARTA POST EDITION 1st - 5th of SEPTEMBER 2018 - Rani Herning Puspita; Sunarti Sunarti (Universitas Bengkulu, 2019)
There are various columns in the newspaper, from the news columns to the opinion column. The speaker letter column contains letters from the speaker which contain various things such as opinions, responses, criticisms, aspirations, suggestions and complaints. Sometimes the language the speaker uses to convey his intent is not explicitly stated. The problems discussed in this study are any speech acts contained in the opinion column of the Jakarta Post newspaper. The objectives of this study are (1) What types of illocutionary speech acts used by speakers in the